Synthesis and Characterization of a Polystyrene-based Scintillator for Gamma Detection - Pancoko, Marliyadi; Hafni Lissa Nuri; Manaf, Azwar; Dimyati, Arbi; Jami, Abdul (BRIN Publishing (Penerbit BRIN), 2023)
This study aimed to create and examine plastic scintillators made from a polystyrene matrix, which are widely used in radiation detection due to their favorable properties such as rapid decay time, low cost, resistance to moisture, and ease of fabrication. The scintillators were doped with p-terphenyl (PTP) and 1,4-bis[2-(phenyloxazolyl)]-benzene (POPOP) using an injection method with an extruder machine. The materials were then characterized using various techniques. Fourier Transform Infrared Spectroscopy (FTIR) revealed the presence of aromatic chains which are essential for the scintillation process. Differential Scanning Calorimetry (DSC) analysis showed stable thermal properties with a glass transition temperature of approximately 100ºC. Scanning Electron Microscopy (SEM) showed that the surface of the polymer is amorphous with small bumps and protrusions likely caused by the PTP and POPOP dopants. The optical evaluation indicated that the sample could absorb UV photons up to 340 nm and emit photons in the wavelength range of 400-500 nm with a peak at 421 nm. Gamma spectra analysis indicated that the plastic scintillators performed well in gamma detection and could be used in a Radiation Portal Monitor (RPM).